2001
DOI: 10.1557/jmr.2001.0339
|View full text |Cite
|
Sign up to set email alerts
|

Model for the robust mechanical behavior of nacre

Abstract: The inelastic deformation of nacre that leads to its structural robustness has been characterized in a recent experimental study. This article develops a model for the inelastic behavior, measured in tension, along the axis of the aragonite plates. The model is based on observations for abalone nacre that the inelasticity is associated with periodic dilatation bands. These bands contain coordinated separations at the periphery of the plates. The separations open as the material strains. The response is attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
238
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(249 citation statements)
references
References 23 publications
10
238
0
1
Order By: Relevance
“…Currey first observed the staggered arrangement of nacre platelets and presented a "Brick and Mortar" model to describe the mechanical behavior of the nacre platelets [15]. Wang et al [22,23] observed the nanoasperities on the platelets and developed a finite element (FE) model based on the friction mechanism. Song et al [24,25] found the mineral bridges (which are mineral connections crossing a protein layer between adjacent mineral platelets) and proposed a "Brick, Bridge, and Mortar" model to interpret the strengthening mechanism of nacre structures.…”
Section: Introductionmentioning
confidence: 99%
“…Currey first observed the staggered arrangement of nacre platelets and presented a "Brick and Mortar" model to describe the mechanical behavior of the nacre platelets [15]. Wang et al [22,23] observed the nanoasperities on the platelets and developed a finite element (FE) model based on the friction mechanism. Song et al [24,25] found the mineral bridges (which are mineral connections crossing a protein layer between adjacent mineral platelets) and proposed a "Brick, Bridge, and Mortar" model to interpret the strengthening mechanism of nacre structures.…”
Section: Introductionmentioning
confidence: 99%
“…1b). Behind the crack tip, the tablets are still in contact and interact through the highly deformable interfaces 26 and associated nanoscale features 27,28 , exerting closure forces, which hinder crack propagation 29 . Furthermore, the wavy shape of the tablets generates progressive interlocking and progressive hardening at the local scale, so that tablet sliding propagates over large volumes around defects and cracks.…”
mentioning
confidence: 99%
“…The 45 work-of-fracture is a measure of material toughness, and the increased toughness also allows reaching higher engineering strength, as observed in Fig 5. We speculate that the observed synergy is related to the surface forces between the components and to the complex role of the soft polysaccharide layer. 50 Evans et al 58,59 suggested that the lubricating effect of the soft domains in nacre leads to shearing and stretching of the organic phase within the slipping reinforcing domains, and provides resistance to deformation. We suggest that the CMC-g-PEG phase works in a similar way in the NFC/CMC-g-PEG 55 nanocomposite, as shown by the low friction.…”
mentioning
confidence: 99%